Selective Solid-Phase Extraction of Meropenem from Human Blood Plasma Using a Molecularly Imprinted Polymer - Lasmaryna Sirumapea; Mohammad Ali Zulfikar; Muhammad Bachri Amran; Anita Alni (Universitas Gadjah Mada, 2021)
This study employed a selective and high adsorption performance for meropenem. Molecularly imprinted polymer for meropenem (MeIP) as the selective sorbent was prepared through a bulk polymerization reaction. Methacrylic acid, ethylene glycol dimethacrylate, benzoyl peroxide, and dimethyl sulfoxide were applied as functional monomer, crosslinker agent, initiator, and solvent, respectively. Scanning electron microscopy, thermogravimetric analysis, Brunauer-Emmett-Teller analysis, and Fourier transform infrared spectroscopy were used to characterize the morphology, pore size, and structure of imprinted polymers. The maximum adsorption capacity was achieved at pH = 3, after 4 h contacted, under 150 rpm, and 25 mg of polymer applied. The maximum adsorption capacity of MeIP for meropenem was 51.963 mg/L; the synthesized polymer had superior selectivity to meropenem compared to that of the other antibiotics (imprinting factor, IF = 2.58). Furthermore, the thermodynamic and kinetic analyses indicated that the results were in accord with the Freundlich model and the pseudo-second-order kinetic model, respectively. MeIP was selective in batch adsorption, and molecularly imprinted solid-phase extraction protocols were selective to meropenem. It was then applied to analyze meropenem in human blood plasma and resulted in 78.52 ± 2.71 of recovery.